Depth‐Dependent Post‐Treatment for Reducing Voltage Loss in Printable Mesoscopic Perovskite Solar Cells. Issue 9 (22nd January 2023) - Xiao, Xufeng; Zhang, Wenhao; Liu, Jiale; Du, Jiankang; Qiu, Cheng; Meng, Ranjun; Mei, Anyi; Han, Hongwei; Hu, Yue
Abstract: The printable mesoscopic perovskite solar cells consisting of a double layer of metal oxides covered by a porous carbon film have attracted attention due to their industrialization advantages. However, the tens‐of‐micrometer thickness of the triple scaffold leads to a challenge for perovskite to crystallize and for the charge carriers to separate and travel to the electrode, which limits the open circuit voltage ( V OC ) of such devices. In this work, a depth‐dependent post‐treatment strategy is demonstrated to synergistically passivate defects and tune interfacial energy band alignment. Two thiophene derivatives, namely 3‐chlorothiophene (3‐CT) and 3‐thiophene ethylenediamine (3‐TEA), are selected for the post‐treatment. Energy‐dispersive X‐ray spectroscopy proves that 3‐CT is uniformly distributed throughout the triple scaffold and effectively passivates the defects of the bulky perovskite, while 3‐TEA reacts rapidly with the loose perovskite in the carbon layer to form 2D perovskite, forming a type II energy band alignment at the perovskite/carbon interface. As a result, the defect‐assisted recombination is suppressed and the interfacial energy band is regulated, increasing the V OC to 1012 mV. The PCE of the devices is enhanced from 16.26% to 18.49%. This depth‐dependent post‐treatment strategy takes advantage of the unique structure and provides a new insight for reducing the voltage loss. Abstract : Two thiophene derivatives, namely 3‐cthlorothiophene and 3‐thiophene ethylenediamine, are selected for the post‐treating the printable mesoscopic solar cells. The different properties of the thiophene derivatives allow them to stay at different depths of the device and play different roles. Ultimately, the defect‐assisted recombination is suppressed and the interfacial energy band is regulated. The resulting devices exhibit improved performance.